Potential Involvement of Organic Anion Transporters in Drug Interactions with Shuganning Injection, a Traditional Chinese Patent Medicine - Bi, Yajuan; Xing, Yanchao; Gui, Chunshan; Tian, Yiqing; Zhang, Mingzhe; Yao, Yao; Hu, Ge; Han, Lifeng; He, Feng; Zhang, Youcai (Planta Medica, 2023)
Traditional Chinese medicine injections have been widely used in China for the treatment of various diseases. Transporter-mediated drug-drug interactions are a major contributor to adverse drug reactions. However, the research on transporter-mediated Traditional Chinese medicine injection-drug interactions is limited. Shuganning injection is a widely used Traditional Chinese medicine injection for treating various liver diseases. In this study, we investigated the inhibitory effect of Shuganning injection and its four main ingredients (baicalin, geniposide, chlorogenic acid, and oroxylin A) on 9 drug transporters. Shuganning injection strongly inhibited organic anion transporter 1 and organic anion transporter 3 with IC50 values < 0.1% (v/v), and moderately inhibited organic anion transporter 2, organic anion transporting-polypeptide 1B1, and organic anion transporting-polypeptide 1B3 with IC50 values < 1.0%. Baicalin, the most abundant bioactive ingredient in the Shuganning injection, was identified as both an inhibitor and substrate of organic anion transporter 1, organic anion transporter 3, and organic anion transporting-polypeptide 1B3. Oroxylin A had the potential to act as both an inhibitor and substrate of organic anion transporting-polypeptide 1B1 and organic anion transporting-polypeptide 1B3. In contrast, geniposide and chlorogenic acid had no significant inhibitory effect on drug transporters. Notably, Shuganning injection markedly altered the pharmacokinetics of furosemide and atorvastatin in rats. Using Shuganning injection as an example, our findings support the implementation of transporter-mediated Traditional Chinese medicine injection-drug interactions in the development of Traditional Chinese medicine injection standards.
Keywords: Transporter; Shuganning injection; drug-drug interaction; Artemisia capillaris; Gardenia jasminoides; Isatis tinctoria; Ganoderma lucidum